The fertility effect of catastrophe: US hurricane births - Richard W. Evans; Yingyao Hu; Zhong Zhao (Institute for the Study of Labor (IZA), 2007)
For years, anecdotal evidence has suggested increased fertility rates resulting from catastrophic events in an area. In this paper, we measure this fertility effect using storm advisory data and fertility data for the Atlantic and Gulf Coast counties of the United States. We find that low-severity storm advisories are associated with a positive and significant fertility effect and that high-severity advisories have a significant negative fertility effect. As the type of advisory goes from least severe to most severe, the fertility effect of the specific advisory type decreases monotonically from positive to negative. We also find that most of the changes in fertility resulting from storm advisories come from couples who have had at least one child already. In addition to our short-term effect estimation, we also test the effects of storm advisories on long run fertility. Our results provide weak evidence at most that the highest severity storm advisories have a permanent negative fertility effect.
Keywords: 330; Fruchtbarkeit; Sturm; Naturkatastrophe; Familienökonomik; USA